The Correlation between Compaction Degree and Performance Life of Asphalt Concrete - Kumalasari, Intan (2008)
Inadequate compaction of wearing course of asphalt concrete is a common phenomenon in road construction. Contractors choose to apply a minimum compaction effort in order to cut costs and speed up construction process. Even though the requirement set by relevant aut})orities such as Jabatan Kerja Raya (JKR), most of the end product failed to achieve this requirement. Inadequate compaction results in pavement with reduced rutting and fatigue life. This study aims to establish a correlation between compaction degree and performance life of asphalt concrete. Such correlations will provide awareness to the practitioner that the void content is a crucial factor in the performance life of asphalt concrete. Three types of tests were carried out to provide quantitative information on performance life of asphalt concrete at various degrees of compaction. The tests were dynamic creep test, fatigue test and wheel tracking test. The mix type is wearing course and the mix designation is asphalt concrete wearing course or ACW20. The material includes asphalt cement, aggregate and cement as filler. Based on JKR recommendation, penetration graded asphalts were used. The sieve analysis was performed according to JKR specifications. From dynamic creep test, the correlation between compaction degree and rutting life obtain_ed was'{ A .=.(4 X 10" 145 } XA 77 • 676 (low porosity), y A= 10-232 XA 120 · 7 (medium porosity) and y A = (3 X 10-256 ) XA 133 08 (high porosity), where y A as rutting I ife in msa and XA as compaction degree in percentage. Low porosity specimen is less susceptibility to rut depth than the high porosity specimen. The correlation between porosity and rate of wheel tracking obtained in this study was Y 8 = 0.0018 X8 1. 8624 with R2 =0.7138, where Y8 is rate of wheel tracking in mm/min and X8 is porosity. This correlation emphasizes that low porosity specimen is more resistant to permanent deformation than high porosity specimen. For fatigue failure, the same trend can be concluded. Keywords Compaction, asphalt concrete, porosity, performance life, rutting, fatigue failure